Sew eco sewing sustainable and re-used materials - Singer, Ruth (A & C Black, 2010)
Sustainable sewing projects don't have to be scratchy hemp skirts and brown patchwork aprons - you could be making beautiful one-off pieces for yourself and your home from unique and unusual eco-friendly recycled or vintage fabrics. A whole new generation of savvy craftsters have been dusting off old sewing machines and revving them up, but they don't want to make just any old thing. This book will guide readers through a series of 20 stylish sewing projects with a focus on sourcing and using sustainable fabrics. The projects teach different aspects of sewing, starting with making cushions fro.
Terminologický slovník
Keywords: šití -- environmentální aspekty; textilní materiály -- environmentální aspekty; ruční práce; recyklované materiály; domácí hospodářství; sewing -- environmental aspects; textile materials -- environmental aspects; fancy work; recycled materials; home economics; příručky; elektronické knihy; handbooks, manuals, etc; electronic books